Satisfaction of participants of the 2nd PKO Bydgoszcz Running Festival (PKO Bydgoski Festiwal Biegowy) - Mateusz Tomanek (Nicolaus Copernicus University in Toruń, 2017)
The sports level of running events is not the only reason to participate in them (often amateurs). A large selection of running events makes it possible to reduce the interest in the event, and this can also be prevented by knowing the expectations of the participants/athletes. The article, which aims to determine the strengths and weaknesses of the running event - the 2nd PKO Bydgoszcz Running Festival (PKO Bydgoski Festiwal Biegowy), aims to present the aspects that need improvement in the next edition. The next task is to present actions to check the level of participants' satisfaction with a particular running event. The research was conducted using the questionnaire method. Due to the cyclical nature of the research, the participants' satisfaction with the previous year was also increased.